The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0103-97332007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization of Bose-Einstein correlations and reconstruction of the source function in hadronic Z-boson decays using the L3 detector

Abstract: Bose-Einstein correlations of pairs of identical charged pions produced in hadronic Z decays are analyzed in terms of various parametrizations. A good description is achieved using a Lévy stable distribution in conjunction with a hadronization model having highly correlated configuration and momentum space, the τ-model. Using these results, the source function is reconstructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…(In fact for an evolving system such as a heavy ion collision, it is not really a surface, since at each time there is a spread out surface due to fluctuations in the last scattering position, and the shape of the surface evolves in time. ) Metzger presented a remarkable analysis of data from the L3 detector at LEP [36]. By a very detailed analysis he showed that deviations from a Gaussian parameterization demonstrated that the the space-time surface of decoupling is consistent with inside-outside cascade dynamics.…”
Section: Hanbury-brown-twiss Interferometrymentioning
confidence: 99%
“…(In fact for an evolving system such as a heavy ion collision, it is not really a surface, since at each time there is a spread out surface due to fluctuations in the last scattering position, and the shape of the surface evolves in time. ) Metzger presented a remarkable analysis of data from the L3 detector at LEP [36]. By a very detailed analysis he showed that deviations from a Gaussian parameterization demonstrated that the the space-time surface of decoupling is consistent with inside-outside cascade dynamics.…”
Section: Hanbury-brown-twiss Interferometrymentioning
confidence: 99%